Effects of Soil–Sand Mixtures on Alchemilla mollis and Geranium psilostemon: A Multi-Criteria Performance Analysis Under Low-Altitude Conditions Using PROMETHEE - Türker Oğuztürk; Cengiz Acar (Horticulturae)
The selection of suitable growing media plays a vital role in the successful adaptation of high-altitude plant species to lowland urban landscapes. This study assessed the morphological and physiological performance of two native perennial species, Alchemilla mollis and Geranium psilostemon, under low-altitude conditions using three different soil–sand (mil) mixtures: TA (50% soil–50% sand), TB (75% soil–25% sand), and TC (100% soil). Over a 17-month period, key plant growth parameters—including height, canopy diameter, leaf number, and chlorophyll concentration—were systematically monitored. Additionally, soil samples were analyzed before and after cultivation to determine pH, total nitrogen, organic matter, organic carbon, phosphorus, and electrical conductivity levels. To evaluate overall performance, the PROMETHEE multi-criteria decision-making (MCDM) method was applied, incorporating 11 criteria spanning plant development, soil quality, and economic considerations. Results revealed that the TC medium offered the most favorable outcomes for both species, particularly in terms of chlorophyll content and biomass accumulation. Conversely, the TB medium supported higher retention of nitrogen and organic matter. While A. mollis exhibited greater resilience under suboptimal conditions, G. psilostemon demonstrated rapid development under favorable settings. These findings underscore the potential of native perennial species in sustainable landscape design and validate the use of MCDM approaches in optimizing plant–soil interactions in horticultural applications.